Impact of Patient Sex on Adverse Events and Unscheduled Utilization of Medical Services in Cancer Patients Undergoing Adjuvant Chemotherapy: A Multicenter Retrospective Cohort Study - Choi, Songji; Seo, Seyoung; Lee, Ju Hyun; Suh, Koung Jin; Kim, Ji-Won; Kim, Jin Won; Kim, Se Hyun; Kim, Yu Jung; Lee, Keun-Wook; Kim, Jwa Hoon; Kim, Tae Won; Hong, Yong Sang; et al. (Cancer research and treatment, 2024)
Purpose The female sex is reported to have a higher risk of adverse events (AEs) from cytotoxic chemotherapy. Few studies examined the sex differences in AEs and their impact on the use of medical services during adjuvant chemotherapy. This sub-study aimed to compare the incidence of any grade and grade ≥ 3 AEs, healthcare utilization, chemotherapy completion rate, and dose intensity according to sex.Materials and Methods This is a sub-study of a multicenter cohort conducted in Korea that evaluated the impact of healthcare reimbursement on AE evaluation in patients who received adjuvant chemotherapy between September 2013 and December 2016 at four hospitals in Korea.Results A total of 1,170 patients with colorectal, gastric, or non–small cell lung cancer were included in the study. Female patients were younger, had fewer comorbidities, and experienced less postoperative weight loss of > 10%. Females had significantly higher rates of any grade AEs including nausea, abdominal pain, stomatitis, vomiting, and neutropenia, and experienced more grade ≥ 3 neutropenia, nausea, and vomiting. The dose intensity of chemotherapy was significantly lower in females, and they also experienced more frequent dose reduction after the first cycle. Moreover, female patients receiving platinum-containing regimens had significantly higher rates of unscheduled outpatient visits.Conclusion Our study found that females experienced a higher incidence of multiple any-grade AEs and severe neutropenia, nausea, and vomiting, across various cancer types, leading to more frequent dose reductions. Physicians should be aware of sex differences in AEs for chemotherapy decisions.